Mechanical stimuli such as shear stress and piezo1 stimulation generate red blood cell extracellular vesicles - Sangha, Gurneet S.; Weber, Callie M.; Sapp, Ryan M.; Setua, Saini; Thangaraju, Kiruphagaran; Pettebone, Morgan; Rogers, Stephen C.; Doctor, Allan; Buehler, Paul W.; Clyne, Alisa M. (Frontiers in Physiology, 2023)
Introduction: Generating physiologically relevant red blood cell extracellular vesicles (RBC-EVs) for mechanistic studies is challenging. Herein, we investigated how to generate and isolate high concentrations of RBC-EVs in vitro via shear stress and mechanosensitive piezo1 ion channel stimulation. Methods: RBC-EVs were generated by applying shear stress or the piezo1-agonist yoda1 to RBCs. We then investigated how piezo1 RBC-EV generation parameters (hematocrit, treatment time, treatment dose), isolation methods (membrane-based affinity, ultrafiltration, ultracentrifugation with and without size exclusion chromatography), and storage conditions impacted RBC-EV yield and purity. Lastly, we used pressure myography to determine how RBC-EVs isolated using different methods affected mouse carotid artery vasodilation. Results: Our results showed that treating RBCs at 6% hematocrit with 10 µM yoda1 for 30 min and isolating RBC-EVs via ultracentrifugation minimized hemolysis, maximized yield and purity, and produced the most consistent RBC-EV preparations. Co-isolated contaminants in impure samples, but not piezo1 RBC-EVs, induced mouse carotid artery vasodilation. Conclusion: This work shows that RBC-EVs can be generated through piezo1 stimulation and may be generated in vivo under physiologic flow conditions. Our studies further emphasize the importance of characterizing EV generation and isolation parameters before using EVs for mechanistic analysis since RBC-EV purity can impact functional outcomes.